(untitled) (Indian Journal of Arid Horticulture, 2025)
Bottle gourd [Lagenaria siceraria (Mol.) Standl.] is gaining importance due to it’s high yield potential, steady market price throughout the season and export potential. It is also a rich source of minerals, protein, carbohydrate and vitamins. It also has a wide medicinal properties such as laxative, digestive and to prevent constipation. Application of nitrogen through inorganic fertilizer can enhance the growth and yield to considerable extent but soil fertility and productivity cannot be retained for a longer period. Integration of chemical fertilizers with organic manures maintains long-term fertility and sustains higher productivity (Pillai et al., 1985). Use of organic manures is not only the liable way for obtaining high productivity with sustainable fertilizer economy but is also a concept of ecological soundness leading to sustainable agriculture (Swaminathan, 1987). Vermicompost is a good organic source of nitrogen and by application of nitrogen through a combination of urea with vermicompost can increase the seed and fruit yield. With this point in view, the present investigations was undertaken to find out the suitable combination of urea and vermicompost in bottle gourd.